Take-up of joint and individual liability loans: an analysis with laboratory experiments - Susmita Baulia (Aboa Centre for Economics (ACE), 2017)
This paper reports a study on decision-making by borrowers regarding take-up of different loan types in a laboratory microfinance experiment setting. I hypothesize that when borrowers are offered a flexible choice of different loan types (here, individual liability (IL) and joint liability (JL)), then they are able to self-select their desirable loan and this could lead to higher overall take-up of loans. I find evidence that loan take-up rate is significantly higher when the choice-set becomes more flexible with additional provision of a second loan type. Further evidence shows that in a setting where moral hazard and free-riding can be eliminated, JL type is more popular among borrowers when both loans are available in the choice-set; this indicates that when borrowers can make sure that partners would not be able to cheat, then JL type could excel in take-up rate. On controlling for risk and selfishness, results suggest that highly risk-averse borrowers mostly stay away from any loan type and prefer safer and unprofitable outside income options. Less selfish borrowers show signs of higher inclination in taking up JL loan, compared to others. Investigating the interaction between discount rate and selfishness, I find that JL is either desirable by those who are selfish yet patient enough to reap the long run benefits of JL loan through its dynamic incentives that reduces the risk of repayment, or by those who are impatient but are less selfish. The results collectively imply that microloan types need to be customized according to the heterogeneous preferences of the borrowers; also, there needs to be enough flexibility in the offered choice-set for better self-selection.
Keywords: C90; D81; G21; I38; O21; 330; Microloan; Laboratory experiment; Loan take-up; Development policy